Il «Vangelo della famiglia»: Aspetti biblico-teologici del racconto di Tobia e Sara - De Virgilio, Giuseppe (Alpha Omega, 2022)
Summary: The article explores the biblical-theological aspects of the book of Tobias as a contribution to reflection on the biblical theology of the family. This study pursues a double purpose: a) to grasp the biblical-theological value of family love and its vocational connotation in the divine plan; b) reflect on the sacredness of the family as an authentic "Gospel" which shines with its witness for the people of our time. These purposes are evoked in the didactic account of Tobias and Sarah, which refers to the original family institution of the creative act of God (cf. Gen 1-2) and describes the religiosity of the believer as an expression of his fidelity to God and to his mercy. The path is divided into three stages as follows: I. The Gospel of the family and the family as "Gospel"; II. The uplifting tale of family love: Tobias and Sarah; III. Updates.